Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(2.\left(x+\frac{2}{5}\right)+1\frac{1}{4}=\frac{11}{20}\)
\(2.\left(x+\frac{2}{5}\right)+\frac{5}{4}=\frac{11}{20}\)
\(2.\left(x+\frac{2}{5}\right)=\frac{-7}{10}\)
\(x+\frac{2}{5}=\frac{-7}{20}\)
\(x=\frac{-13}{20}\)
Vậy \(x=\frac{-13}{20}\)
b)\(x-1\frac{1}{8}-\frac{2}{3}x-\frac{5}{6}x=75\%\)
\(\left(x-\frac{2}{3}x-\frac{5}{6}x\right)-\frac{9}{8}=\frac{3}{4}\)
\(\frac{-1}{2}x-\frac{9}{8}=\frac{3}{4}\)
\(\frac{-1}{2}x=\frac{15}{8}\)
\(x=\frac{-15}{4}\)
Vậy \(x=\frac{-15}{4}\)
f) (2x - 8)(4x + 16) = 0
<=> 2x - 8 = 0 hoặc 4x + 16 = 0
<=> 2x = 0 + 8 hoặc 4x = 0 - 16
<=> 2x = 8 hoặc 4x = -16
<=> x = 4 hoặc x = -4
g) 5x(6x - 12) = 0
<=> 5x = 0 hoặc 6x - 12 = 0
<=> x = 0 hoặc 6x = 0 + 12
<=> x = 0 hoặc 6x = 12
<=> x = 0 hoặc x = 2
h) 7(9 - x)(12 - 6x) = 0
<=> 9 - x = 0 hoặc 12 - 6x = 0
<=> -x = 0 - 9 hoặc -6x = 0 - 12
<=> -x = -9 hoặc -6x = -12
<=> x = 9 hoặc x = 2
a: =>4x-4-3x+6=-5
=>x+2=-5
=>x=-7
b: =>\(-4x-4+8x-24=24\)
=>4x-28=24
=>4x=52
=>x=13
c: \(\Leftrightarrow12x-48+6x-12-16x-48=7\cdot4=28\)
=>2x-108=28
=>2x=136
=>x=68
d: =>2|x-6|=2
=>|x-6|=1
=>x=7 hoặc x=5
e: =>|x+2|=20-6x+6x-24=-4(loại)
8x +8 +20 =4+6x
8x-6x = -24
2x=-24
x = -12
8(x+1)+16+4=4+6x
8x+8+16+4=4+6x
8x-6x =4-16-4
2x =-24
x =-24:2=-12